Prevalence and associated factors of self-reported medical errors and adverse events among operating room nurses in China - Song, Qi; Tang, Juan; Wei, Zhen; Sun, Long (Frontiers in Public Health, 2022)
Background: In recent decades, the prominence of medical errors (MEs) and adverse events (AEs) is fueled by many literatures in the world, which reported a high prevalence of medical errors and adverse events. Operating room nurses (ORNs) were indispensable members of operating process, and any kinds of MEs or AEs from ORNs may cause serious results and even death to the patients. However, to our knowledge, the prevalence and associated factors of MEs and AEs were never reported among ORNs in China, which is the largest country in population and health services quantity in the world. Methods: This is a cross-sectional study, which was conducted among ORNs in China, and 787 valid questionnaires were analyzed in this study. MEs, AEs, gender, age, married status, religious belief, academic degree, manager or not, working years, working hours/week, physical disease, mental health were evaluated in this study. MEs were evaluated by eight questions about the occurrence of eight kinds of MEs for the ORNs. For ORNs with MEs, further questions about clinical harm to the patients were interviewed, which were analyzed AEs. Kessler 10 was used to evaluated the ORNs’ mental health. Logistic regression was conducted to examine the factors associated with MEs and AEs. Results: The prevalence of MEs and AEs were 27.7% and 13.9% among ORNs, respectively. The most frequent MEs occurred among ORNs were about surgical instruments (9.1%), disinfection (9.0%), equipment and consumables (8.9%), and specimen management (7.8%). MEs were positively associated with lower working years, poor mental health, and physical disease. Physical disease was positively associated with AEs. Conclusions: The prevalence of perceived MEs and AEs was in higher level than other kinds of nurses. Fresh ORNs with physical and mental health problems were the risk population for MEs, and ORNs with physical disease were in higher risk of AEs. All the findings implied us that MEs and AEs were an important issue for ORNs, and ORNs with physical and mental health problems should be paid attention to control MEs and AEs.